2018
DOI: 10.1111/psyg.12302
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue in Parkinson's disease: concepts and clinical approach

Abstract: Parkinson's disease (PD) is a progressive neurological disorder characterized by a large number of motor and non-motor features. Fatigue is one of the most common and most disabling symptoms among patients with PD, and it has a significant impact on their quality of life. Although fatigue has been recognized for a long time, its pathophysiology remains poorly understood, and there is no evidence to support any therapeutic approach in PD patients. Expert consensus on case definition and diagnostic criteria for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 81 publications
0
27
0
Order By: Relevance
“…Some studies found that the cerebellum played an important role in action control and motor learning, which may be involved in the model of central fatigue (36). In addition, a previous study reported that fatigue is associated with dopaminergic dysfunction within the basal ganglia in PD patients (9). Additionally, the neuroimaging study also demonstrated that SCA3 patients had dopaminergic dysfunction (6).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Some studies found that the cerebellum played an important role in action control and motor learning, which may be involved in the model of central fatigue (36). In addition, a previous study reported that fatigue is associated with dopaminergic dysfunction within the basal ganglia in PD patients (9). Additionally, the neuroimaging study also demonstrated that SCA3 patients had dopaminergic dysfunction (6).…”
Section: Discussionmentioning
confidence: 98%
“…SCA3 has a wide range of clinical manifestations, and cerebellar ataxia is the core symptom, including progressive dysarthria, unstable walking and hand clumsiness (4). In addition, other symptoms, including extra-cerebellar signs and non-motor symptoms, are also reported in SCA3 patients, such as parkinsonism, pyramidal signs, oculomotor deficits, dystonia, cognitive impairment, fatigue, sleep disorders, and psychiatric changes (59). A majority of non-ataxia symptoms appear insidiously and are often underestimated in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, a treatment for fatigue in SCA3 patients has not yet been reported. However, standardized treatment for fatigue in PD patients does exist, inclusive of a balanced medication regime targeting movement disorder (e.g., dopaminergic agents) and depression (e.g., psychostimulants and antidepressants) combined with a rehabilitation program (e.g., cognitive behavior therapy and graded exercise) (5). Furthermore, research has demonstrated that pharmacological (modafinil) and non-pharmacological (respiratory exercise and repetitive transcranial magnetic stimulation) management may be possible treatment options for fatigue in ALS patients (43).…”
Section: Discussionmentioning
confidence: 99%
“…Fatigue, which is clinically defined as difficulty in the initiation of or sustainment of voluntary mental and physical activities (4), is a subjective experience and common in neurodegenerative disorders such as Parkinson's disease (PD) and amyotrophic lateral sclerosis (ALS) (5)(6)(7)(8)(9)(10)(11)(12). As a common symptom, fatigue was found to have great impact on the quality of life in PD (13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Fatigue in Parkinson's disease (PD) has a lifetime prevalence of more than 50% [1], and is a significant contributor to decline in health-related quality of life (HR-QOL) [2]. Despite the breadth of this problem, fatigue in PD remains poorly understood, and there are few effective therapies [3]. The etiology of fatigue in PD is likely multifactorial, including underlying neurodegeneration, other non-motor problems that may manifest as, or be comorbid with, fatigue (sleep problems, depression, apathy), and the effects of PD medications [3]; many patients also experience idiopathic fatigue or fatigue of unknown cause.…”
Section: Introductionmentioning
confidence: 99%